Pengaruh Penerapan Standar Komunikasi Defisit Perawatan Diri terhadap Kemandirian Merawat Diri pada Pasien Skizofrenia di Ruang Rawat Inap Delta Rumah Sakit Jiwa Daerah Provinsi Jambi - Rd Hari Periza W; Rahmi Dwi Yanti; Vevi Suryenti Putri (Jurnal Akademika Baiturrahim Jambi, 2021)
Schizophrenic is a disease that affects the brain and causes strange, disturbed thought, perception, emotion, movement, and behavior. These case made patient experiencing significant self-care deficit, causing patients did not pay attention to hygiene. The nursing tread to deal the patient with schizophrenic is the application of self-care deficit communication standard. This study aimed to indicated the influence of applying self-care deficit communication strategies to self-care independence in schizophrenic patient. This study used quantitative research by using pre pre-experiment design, with one group pretest posttest was used. The number of samples were 20 persons. This study used purposive sampling technique. It was conducted on January 1th - 15th 2020. The data were collected by an instrument in the form of observation sheets. It were analyzed by the Wilcoxon test. The findings, The average self-care independence before implementing the self-care communication deficit standard with an average value (3.00) to (4.00) after the application of communication standards is given. There is a difference in the application of the self-care deficit communication standard with a P-value = 0.001